Leishmaniasis: Recent epidemiological studies in the Middle East - Knight, Chinyere A.; Harris, David R.; Alshammari, Shifaa O.; Gugssa, Ayele; Young, Todd; Lee, Clarence M. (Frontiers in Microbiology, 2023)
Leishmaniasis, one of the most neglected diseases, is the third most important vector-borne disease worldwide. The disease has global impacts and severity of the infection is greatest in the Middle East. The agent of infection is a protozoan parasite of the genus, Leishmania and is generally transmitted by sandflies. In humans, there are three clinical forms of the infection: 1) cutaneous (CL), 2) mucocutaneous (ML), and 3) visceral leishmaniasis (VL). The aim of this review is to discuss the current epidemiological status of leishmaniasis in Saudi Arabia, Iraq, Syria, and Yemen with a consideration of treatment options. The elevated risk of Leishmaniasis disease is influenced by transmission of the disease across endemic countries into neighboring non-infected regions.